Current Perspective About the Effect of a Ketogenic Diet on Oxidative Stress – a Review - Natalia Drabińska (Polish Journal of Food and Nutrition Sciences)
Oxidative stress (OS) plays a pivotal role in the development of many diseases. Therefore, many efforts have been undertaken to minimize the consequences of OS or improve antioxidant defence systems. One solution expected to improve redox homeostasis is the ketogenic diet (KD). KD is a low-carbohydrate, high-fat diet leading to a ketosis state. The shift in metabolism occurring in ketosis can affect the reactive oxygen species (ROS)-producing pathways and influence the expression of enzymes involved in redox homeostasis. Therefore, this review summarizes and discusses existing knowledge about KD and ROS homeostasis. The available tools for evaluating OS status are presented, listing their potential and drawbacks. An important aspect is the summary of the current knowledge about the effect of KD on OS conducted in vitro, in vivo, and in clinical trials. Finally, the review addresses future studies needed to understand the connection between KD and OS.